Perkembangan dan Pelestarian Kain Sasirangan Pewarna Alam di Kota Banjarmasin - Hartiningsih (Jurnal Kebijakan Pembangunan, 2020)
Naturally dyed Sasirangan is one of the cultural heritage of the Banjar Empire. Originally, the Sasirangan was made using natural dyes. Nowadays, the Sasirangan made by synthetic dyes. The synthetic dyes can produce more various and brighter colors, which is more interesting for the consumer. The synthetic dyes have been reduced and lowered the interest of natural dyed Sasirangan fabric. Along with the less interest in natural dyed Sasirangan fabric, the craftsmen reduction, and other various impacts, it is concerned that the natural dyed Sasirangan fabric which is a heritage will be extinct. Therefore, this research was conducted to give an overview of the existence of the natural dyed Sasirangan fabric and the roles of the government, the craftsmen, as well as the society in their effort to preserve it. The research method is qualitative descriptive. The result shows that the existence of the natural dyed Sasirangan fabric has been significantly increased both for its quantity, which is the rise of the craftsmen’s number, as well as its quality such as the motives diversity and the coloring quality which does not wear off easily. The effort of the government, the craftsmen, and the society in preserving Sasirangan fabric is quite diverse, from the coaching, the training for the general public, the housewives, also the students in the school environment. Even, for maintaining the Sasirangan fabric preservation, the Banjarmasin City government issued a policy in the form of a circular which obliges all the state civil apparatus in the environment of Banjarmasin City government to wear clothing made of natural dyed Sasirangan fabric on a certain day of each month. Keywords: Sasirangan Fabric, Natural Dyes, Preservation, Banjar Culture ABSTRAK Kain sasirangan pewarna alam merupakan salah satu warisan budaya Kerajaan Banjar. Kain sasirangan semula dibuat dengan menggunakan pewarna alam. Seiring dengan perkembangan zaman kain sasirangan kemudian dibuat dengan menggunakan zat pewarna sintetis. Pewarna sintetis dapat menghasilkan warna yang lebih beragam dan cerah sehingga lebih banyak diminati konsumen, sehingga minat terhadap sasirangan pewarn alam semakin berkurang. Hal ini pada akhirnya mengakibatkan terus berkurangnya pengrajin sasirangan pewarna alam dan dikhawatirkan kain sasirangan pewarna alam yang merupakan warisan leluhur akan punah. Penelitian ini dilakukan untuk memberikan gambaran keberadaan kain sasirangan pewarna alam dan upaya pelestariannya oleh pemerintah, pengrajin dan masyarakat. Metode penelitian adalah deskriptif kualitatif. Hasil penelitian menunjukkan produksi kain sasirangan pewarna alam mengalami peningkatan yang cukup signifikan. Kualitasnya juga meningkat dalam hal variasi motif dan warna yang tidak mudah luntur. Upaya pelestarian dari pemerintah, pengrajin dan elemen masyarakat meliputi pembinaan dan pelatihan terhadap masyarakat umum, ibu-ibu rumah tangga, sampai pada anak didik di lingkungan sekolah. Pemerintah Kota Banjarmasin juga mengeluarkan kebijakan berupa Surat Edaran yang mewajibkan seluruh ASN di lingkungan Pemerintah Kota Banjarmasin menggunakan pakaian berbahan kain sasirangan pewarna alam pada hari tertentu dalam setiap bulannya. Kata Kunci: Kain Sasirangan, Pewarna Alam, Pelestarian, Budaya Banjar.